Laboratory Screening of Inherited Thrombotic Syndromes - Mannucci, Pier Mannuccio; Tripodi, Armando (Thrombosis and Haemostasis, 1987)
The prevalence of inherited thrombotic syndromes in the general population (1 in 2,500/5,000) appears to be higher than that of inherited bleeding disorders. The problems of their laboratory diagnosis are reviewed and a screening procedure is proposed. The most important candidates for screening are patients with unexplained venous thromboembolism at ages of less than 40-45 years, particularly when thrombotic episodes are recurrent. Screening must start from the exclusion of common acquired causes of thrombophilia. A negative family history does not exclude inherited thrombophilia, because the defects have a low penetrance and fresh mutations may have occurred in the propositi. Laboratory screening is based on a two-step procedure. The first step is aimed at detecting, preferably with specific functional assays. the most frequent and well established causes of inherited thrombophilia, i.e. deficiencies or dysfunctions of antithrombin III, protein C, protein S, plasminogen and fibrinogen. The tests included in the second step of the screening are aimed at detecting the less common or less well established causes of inherited thrombophitia (low heparin cofactor II, defective release of tissue plasminogen activator, and high plasminogen activator inhibitor). The simplest, more reliable and specific assay methods to be used in laboratory practice are recommended.
Keywords: Inherited thrombophilia; Antithrombin III; Protein C; Protein S; Heparin cofactor II; Plasminogen; Dysfibrinogenemia; Tissue plasminogen activator